The Effect of Western Architecture on Losing Local Architecture Identity - Wrya Sabir Abdullah1,a,* (Sulaimani Journal for Engineering Sciences)
Architecture represents the most effective visual element of civilization that can distinguish the identity of its region as well as of its people. Every architecture that shows the power and identity of the nations have been formed according to the ideas and identity of both the architects and people who were living from the formation of its civilization. This paper studies the concept of local architectural identity and the role of western and global architectural styles on changing its identity in Kurdistan region of Iraq. This study is an attempt to stand against the continuous flow of western effects on the identity of local architecture in Kurdistan Region of Iraq. It aims to show that omitting local identity and spreading western identity in architecture affects local culture and the result will be the formation of multiculturalism in the region, this in turn would make the next generations not to recognize their original identity of local architecture. This paper studies local architecture identity in Erbil and Sulaimaniyah cities showing how local architecture has distorted during contemporary architecture developments especially within the contemporary investment Residential projects. This study adopted a comparative qualitative methodology that makes comparison between traditional urban and architectural samples in both cities with samples that have been design after 2003 to show how western architecture has influenced local architecture identity. The results show that mostly designed residential complexes and housing projects adopted modern western styles and ignored original local architecture identity on both urban and architecture scales.